PEMETAAN DAERAH RAWAN LONGSOR LAHAN DI KECAMATAN CENRANA KABUPATEN MAROS - Invanni, Ichsan; Zhiddiq, Sulaiman; Fitriani, Fitriani (UNIVERSITAS NEGERI MAKASSAR, 2024)
ABSTRACTLandslides are events caused natural or non-natural factor, or human factors and human actions, which threaten or disrupt life, resulting in material damage, enviromental damage and even causing loss of life. This study aims to (1) Describe the land in Cenrana District, Maros Regency (2) Know about the causes of land landslides in Cenrana District, Maros Regency and (3) Know about the distribution and level of landslide hazard in Cenrana District, Maros Regency. This type of research is descriptive qualitative research. With five variables used, namely rainfall, slope, land use, rock type and soil type. The data collection technique in this research is a direct survey technique in the field and documentation. Data analysis in this research is a cartographic technique, namely by overlaying several thematic maps.The results of the research show that in the map of the level of landslide susceptibility in Cenrana District, Maros Regency there are 4th classes of vulnerability produced by the results of map overlay analysis in Cenrana District. It can be seen in table 4.6 that the low level of landslide susceptibility has an area of441.29 Ha or 2.12%, level medium landslide prone has an area of 9.128 Ha or 43.78%, high landslide prone has an area of 11.229,31 Ha or 53.85%, while very high landslide prone has an area of 52.80 or 0.25%.